Safety and Effectiveness of Large Gel Particle Hyaluronic Acid with Lidocaine for Correction of Midface Volume Loss. Issue 11 (1st November 2013) - Bertucci, Vince; Lin, Xiaoming; Axford‐Gatley, Robert A.; Theisen, Michael J.; Swift, Arthur
Abstract : Background: Midface volume loss and contour deficiency are often treated using soft‐tissue fillers capable of elevating and supporting facial features. Objective: To evaluate the effectiveness and safety of large gel particle hyaluronic acid with 0.3% lidocaine (LGP‐HA‐L) for the treatment of midface volume loss or contour deficiency. Methods and Materials: This 24‐week, open‐label study recruited adults aged 18 to 65 with bilateral moderate to substantial midface volume loss or contour deficiency (Medicis Midface Volume Scale (MMVS) score 3–4). The primary effectiveness measure was MMVS response (≥1‐grade improvement) 8 weeks after treatment according to evaluators blinded to injection volume. Results: All enrolled patients ( n  = 40; 85.0% female; mean ± SD age 53.1 ± 7.0 years) completed the study. Mean ± SD injected volume for both sides of the midface was 5.3 ± 2.5 mL. Week 8 MMVS response rates were 97.5% according to blinded evaluators and treating investigators and 90.0% according to patients; week 24 rates were 90.0%, 92.5%, and 82.5%, respectively. Global Aesthetic Improvement Scale response rates were 95.0% to 100.0% throughout the study. Adverse events were reported in 60.0% of patients and were mild or moderate; all resolved by study end and most within 1 week. Conclusion: Midface volume loss or contour deficiency may be safely and effectively corrected using LGP‐HA‐L.